2017
DOI: 10.1039/c7ra09243a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of metal–organic frameworks fabricated by microwave-assisted ball milling for adsorptive removal of Congo red from aqueous solutions

Abstract: In this study, four metal–organic frameworks (MOFs) were prepared using a simple, low-cost, and high-efficiency technique utilizing simple carboxylic acids and metal salts by microwave-assisted ball milling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…Fe-MOFs were synthesized by microwave-assisted ball milling on the basis of a previously reported way [ 48 ]. H 3 BTC (98%) and FeSO 4 ·7H 2 O were purchased from Shanghai Aladdin Biological Technology Co., Ltd. (Shanghai, China), while potassium dichromate (≥99.8%) was purchased from Tianjin Zhiyuan Chemical Reagent Co., Ltd. (Tianjin, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fe-MOFs were synthesized by microwave-assisted ball milling on the basis of a previously reported way [ 48 ]. H 3 BTC (98%) and FeSO 4 ·7H 2 O were purchased from Shanghai Aladdin Biological Technology Co., Ltd. (Shanghai, China), while potassium dichromate (≥99.8%) was purchased from Tianjin Zhiyuan Chemical Reagent Co., Ltd. (Tianjin, China).…”
Section: Methodsmentioning
confidence: 99%
“…Microwave-assisted ball milling was first described by our laboratory and is based on a solid-liquid ball-milling (MSBM) approach that involves using a ball-milling machine in a microwave oven [ 41 , 42 , 43 , 44 , 45 , 46 ]. The coupling of mechanical milling with microwaves enables certain nanocrystal materials, such as magnetic and metal oxidation ferrite, to be generated at room temperature [ 47 , 48 , 49 ]. In the present study, MOF-based adsorptive removal of hazardous compounds, including RhB, Orange II, and CR, from aqueous media was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown the synthesized of CuBTc MOF and its use in various applications, such as being used as an ion exchanger, adsorption agent, reduction agent, and antioxidant agent [6][7][8][9][10][11]. However, there are still no studies investigating the potential of CuBTc-MOF to catalyze biodiesel production thus far.…”
Section: Introductionmentioning
confidence: 99%
“…The intensities of all crystallinity peaks which increased gradually in short periods could be attributed to the fast heating precursor and avoid thermal gradients [20,21]. It also demonstrated that the increased irradiation time leads to high yields and Journal of Nanomaterials larger crystals [22]. It indicated that microwave heating was more effective than the convenient heating.…”
Section: Resultsmentioning
confidence: 91%